GUIDED INQUIRY-BASED EARTHQUAKE MEDIA: ENHANCING SCIENCE LITERACY AND CRITICAL THINKING IN POST-LIQUEFACTION SCHOOLS - Arum Maulidiyah; Unggul Wahyono; Haeruddin; Sahrul Saehana; I Komang Werdhiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of guided inquiry-based earthquake media on the scientific literacy and critical thinking skills of elementary school students in the Petobo liquefaction-affected area, Palu City. The low scientific literacy and disaster preparedness of students after the 2018 earthquake became the basis of this study. The method used was a quasi-experimental with a Non-Equivalent Control Group design, involving 53 sixth grade students. The experimental group implemented guided inquiry learning through the creation of a simple seismograph, while the control group used conventional learning. The results showed an increase in scientific literacy and critical thinking in the experimental group was higher than the control group, with a significant difference based on statistical tests and learning effectiveness that was classified as moderate to high. It was concluded that guided inquiry-based earthquake media was more effective in improving scientific literacy and critical thinking skills of students in disaster-affected areas.